Grounding United States policies and programs in soil carbon science: strengths, limitations, and opportunities - Gelardi, Danielle L.; Rath, Daniel; Kruger, Chad E. (Frontiers in Sustainable Food Systems, 2023)
The advent of “natural climate solutions” and “climate smart agriculture” has increased interest in managing agricultural lands to sequester soil carbon and mitigate climate change. This has led to enormous opportunities for soil scientists and growers alike, as new soil carbon initiatives are created by public, private, and philanthropic entities. It has also led to confusion over what is possible or practical to achieve through agricultural management, as soil carbon formation and storage is complex, and its response to management is context-dependent. This can pose challenges to decision makers tasked with creating defensible, science-informed policies and programs for building and protecting soil carbon. Here we summarize the science concerning the potential for agricultural soils to serve as a natural climate solution, in order to frame a discussion of current approaches in United States (US) policy and practice. We examine existing strategies such as soil health initiatives and direct incentive payments, as well as emerging schemes such as carbon markets and crop insurance reform. We suggest future directions for each strategy, and make recommendations for synthesizing approaches into a cohesive US policy portfolio. Guiding principles for this discussion include the notions that (i) climate change adaptation must be prioritized alongside climate change mitigation; (ii) soil carbon sequestration must be paired with greenhouse gas emission reductions; (iii) structural issues and barriers to adoption must be addressed as part of all policies and programs; (iv) practice- and place-specific programs must be administered in lieu of one-size-fits-all prescriptions; and (v) soil carbon science is not yet sufficiently advanced for the accounting and contractual frameworks proposed in cap-and-trade or regulatory approaches.